Pengaruh Atraksi Wisata dan Harga Terhadap Kepuasan yang Berdampak pada Minat Kunjung Wisatawan Taman Mini Indonesia Indah (TMII), Jakarta - Nurbaeti, Nurbaeti; Amrullah, Amrullah; Asmaniati, Fetty; Osman, Ismeth Emier (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2022)
This study aims to determine the effect of tourist attractions and prices on visiting intentions through tourist satisfaction. This research is a quantitative descriptive type with path analysis using Smart PLS. Data collection techniques by distributing questionnaires with sampling using accidental sampling. The population in this study amounted to 746,368 people. At the same time, the number of samples determined by the Slovin formula is 100 people. The results showed: (1) Attractions and prices partially have a significant effect on satisfaction; (2) Attractions and prices partially have a significant effect on visiting intentions; (3) Partial satisfaction has a significant effect on visiting intentions; (4) Attractions and prices partially have a significant effect on the intention to visit through satisfaction. TMII managers are expected to maximize the function of the traditional house building as a display of forms from Indonesia to increase the number of regional tourist visits. It is hoped that the Ministry of Tourism can increase the number of visits to TMII by working with YouTubers or celebrities to promote TMII. Keywords: Tourist Attractions, Prices, Satisfaction, Interest in Visiting